Experiences of oral health: before, during and after becoming a regular user of GC Tooth Mousse Plus® - Alexandra Sbaraini; Geoffrey G. Adams; Eric C. Reynolds (BMC, 2021)
Abstract Background Clinical trials and laboratory studies from around the world have shown that GC Tooth Mousse Plus® (TMP) is effective in protecting teeth from tooth decay and erosion, buffering dental plaque pH, remineralising white spot lesions and reducing dentine hypersensitivity. However, no other study has assessed the experiences of oral health, before, during and after individuals becoming regular users of TMP. The aim of this study was to identify how participants' oral health status changed after introducing TMP into their oral hygiene routine. Methods A qualitative study using Charmaz's grounded theory methodology was conducted. Fifteen purposively sampled regular users of TMP were interviewed. Transcripts were analysed after each interview. Data analysis consisted of transcript coding, detailed memo writing, and data interpretation. Results Participants described their experiences of oral health and disease, before, during and after introducing TMP into their daily oral hygiene routine, together with the historical, biological, financial, psychosocial, and habitual dimensions of their experiences. Before becoming a regular user of TMP, participants described themselves as having a damaged mouth with vulnerable teeth, dry mouth, and sensitivity. Various aspects of participants' histories were relevant, such as, family history and history of oral disease. Having a damaged mouth with vulnerable teeth, dry mouth and sensitivity was explained by those elements. Despite some initial barriers, once being prescribed TMP by a dental professional, a three-fold process of change was initiated: starting a new oral hygiene routine, persevering daily, and experiencing reinforcing outcomes. This process led to a fundamental lifestyle change. Participants transitioned from having a damaged mouth with vulnerable teeth to having a comfortable mouth with strong teeth; at the same time participants felt empowered by this newly found status of being able to keep their teeth for life. Barriers and facilitators for incorporating TMP on daily oral hygiene routine were also identified. Conclusions Participants valued having a comfortable mouth with strong teeth, which did not require repeated restorations. Seeing concrete results in their mouths and experiencing a more comfortable mouth boosted adherence to daily applications of TMP, which was maintained over time.